2020
DOI: 10.1111/1462-2920.14967
|View full text |Cite
|
Sign up to set email alerts
|

In hot water: effects of climate change on Vibrio–human interactions

Abstract: Sea level rise and the anthropogenic warming of the world's oceans is not only an environmental tragedy, but these changes also result in a significant threat to public health. Along with coastal flooding and the encroachment of saltwater farther inland comes an increased risk of human interaction with pathogenic Vibrio species, such as Vibrio cholerae, V. vulnificus and V. parahaemolyticus. This minireview examines the current literature for updates on the climatic changes and practices that impact the locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 80 publications
0
72
0
1
Order By: Relevance
“…might be increased in warmer waters due to the enhanced expression of virulence genes, thus reflecting higher rates of infection and a threat to public health. This is particularly alarming in the framework of climate change, but also in environments characterized by naturally warmer waters, such as the GB, where temperatures above 20 °C were recurrent in all sampling sites during the analyzed period [ 9 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…might be increased in warmer waters due to the enhanced expression of virulence genes, thus reflecting higher rates of infection and a threat to public health. This is particularly alarming in the framework of climate change, but also in environments characterized by naturally warmer waters, such as the GB, where temperatures above 20 °C were recurrent in all sampling sites during the analyzed period [ 9 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the genus Vibrio along with 13 other pathogens are accountable for more than 95% of foodborne infections and subsequent hospitalizations in the United States and responsible for 98% of deaths [ 8 ]. Moreover, extraintestinal infections caused by Vibrio spp., such as ear and wound infections, have been gaining more attention in view of the consequences of climate change, which have been linked to a rise in such cases [ 5 , 9 ]. There is currently an absence of surveillance systems dedicated to Vibrio illnesses outside the United States, a country where these data have been gathered since 1989 through “The Cholera and Other Vibrio Illness Surveillance” (COVIS) system [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens can also inflict expensive losses on aquaculture enterprises. Given their impact on human and animal health and the relative ease of their culture, vibrios have been well studied [18,19]. In this regard, different species of Vibrio form cohesive groups within which they easily exchange genetic elements to confer greater antibiotic resistance, as well as regulate virulence [20].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance for dermatologists are V. parahaemolyticus and V. vulnificus. The changing climate has extended the seasons of infectivity of these species, and studies on the incidence of their associated diseases in the USA have found increased abundance along the Pacific coast and in non-coastal states [73]. Already, these altered infection patterns have resulted in increased hospitalizations for dermatologic conditions, including wound infections, cellulitis, and sepsis [74,75], and inpatient dermatologists should expect to see continued rises in the frequency of such cases.…”
Section: Increased Temperatures and Extreme Weather Eventsmentioning
confidence: 99%